Corruption, Governmental Activities, and Markets - Tanzi, Vito. (Washington, D.C. : International Monetary Fund, 1994)
Paper discusses the factors that contribute to the spread of corruption as well as the implications of corruption for markets and for public sector activities. It is argued that corruption can be contained mainly by a scaling down of the public sector activities that stimulate its growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet